Digital technologies in Physics education: an experience report using the Kahoot as a tool of evaluation (Research, Society and Development, 2018)
In view of the increase in research on the use of strategy as a teaching strategy, some technological resources have emerged that aim to use the methodology in the classroom. In this sense, this work aims to describe the potential of Kahoot, one of the technological resources, as the evaluation tool in gamified activities. In this sense, the objective of this study in the middle-per-explorer and the practice for the practical experience in the middle use of education in the middle of general education of Fortaleza/CE. The easy-to-access data collection instrument was an evaluation questionnaire using a five-point Likert. The results were obtained with the aid of a potential questionnaire as an evaluation instrument in gamification activities, by allowing feedback of students' answers, punctuation and ranking with instantaneous classification of students. This is the use of the use to the use of the Kahoot, associated with the teacher's substantial knowledge of gamification, may possible for the mayor possible, attractive and pleasureosa to the students. Finally, it is believed that the effective use of digital technologies in the classroom must always have an adequate and consistent teaching / learning methodology.